WASh multicentre randomised controlled trial: water-assisted sigmoidoscopy in English NHS bowel scope screening. Issue 5 (7th September 2020) - Rutter, Matthew D; Evans, Rachel; Hoare, Zoe; Von Wagner, Christian; Deane, Jill; Esmaily, Shiran; Larkin, Tony; Edwards, Rhiannon; Yeo, Seow Tien; Spencer, Llinos Haf; Holmes, Emily; Saunders, Brian P; et al.
Abstract : Objectives: The English Bowel Cancer Screening Programme invites 55 year olds for a sigmoidoscopy (Bowel Scope Screening (BSS)), aiming to resect premalignant polyps, thus reducing cancer incidence. A national patient survey indicated higher procedural pain than anticipated, potentially impacting on screening compliance and effectiveness. We aimed to assess whether water-assisted sigmoidoscopy (WAS), as opposed to standard CO2 technique, improved procedural pain and detection of adenomatous polyps. Design: The WASh (Water-Assisted Sigmoidoscopy) trial was a multicentre, single-blind, randomised control trial for people undergoing BSS. Participants were randomised to either receive WAS or CO2 from five sites across England. The primary outcome measure was patient-reported moderate/severe pain, as assessed by patients on a standard Likert scale post procedure prior to discharge. The key secondary outcome was adenoma detection rate (ADR). The costs of each technique were also measured. Results: 1123 participants (50% women, mean age 55) were randomised (561 WAS, 562 CO2 ). We found no difference in patient-reported moderate/severe pain between WAS and CO2 (14% in WAS, 15% in CO2; p=0.47). ADR was 15% in the CO2 arm and 11% in the WAS arm (p=0.03); however, it remained above the minimum national performance standard in both arms. There was no statistical difference in mean number of adenomas nor overall polyp detection rate. There was negligible cost difference between the two techniques. Conclusion: In the context of enema-prepared unsedated screening sigmoidoscopies performed by screening-accredited endoscopists, no difference in patient-reported pain was seen when using either a CO2 or WAS intubation technique. Trial registration number: ISRCTN81466870 .